1988
DOI: 10.1007/bf01243380
|View full text |Cite
|
Sign up to set email alerts
|

In vivo labelling of rat brain dopamine D-2 receptors

Abstract: The stereospecific blockade by raclopride and FLB472 (the R enantiomer of raclopride) of the specific in vivo binding of [3H]-spiperone, [3H]-N,N-propylnorapomorphine (NPA) and [3H]-raclopride was studied in seven brain regions (e.g., caudate nucleus, olfactory tubercle, septum, hippocampus, frontal cortex, substantia nigra, pituitary gland) of the male albino rat. The binding of all three ligands was dose-dependently blocked by raclopride and FLB472. The blockade by FLB472 occurred at doses 50-100 times highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…The PET study showed that receptor occupancy increased dose dependently. These dose responses of the receptor occupancy corresponded with that of previous study examined after intravenous administration of raclopride (Kohler & Karlsson-Boethius, 1988;Wong et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…The PET study showed that receptor occupancy increased dose dependently. These dose responses of the receptor occupancy corresponded with that of previous study examined after intravenous administration of raclopride (Kohler & Karlsson-Boethius, 1988;Wong et al, 2018).…”
Section: Discussionsupporting
confidence: 82%